Recovery of Human Metapneumovirus Genetic Lineages A and B from Cloned cDNA - Herfst, Sander; de Graaf, Miranda; Schickli, Jeanne H.; Tang, Roderick S.; Kaur, Jasmine; Yang, Chin-Fen; Spaete, Richard R.; Haller, Aurelia A.; van den Hoogen, Bernadette G.; Osterhaus, Albert D. M. E.; Fouchier, Ron A. M. (Journal of Virology, 2004)
Article Usage Stats Services JVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue JVI About JVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0022-538X Online ISSN: 1098-5514 Copyright © 2014 by the American Society for Microbiology. For an alternate route to JVI .asm.org, visit: JVI